Pengaruh Self Confidence terhadap Hasil Belajar Matematika Siswa Kelas 8A SMP Ta’mirul Islam Surakarta - Istna Hani Salami; Fuad Lucky Atmaja (Griya Journal of Mathematics Education and Application, 2026)
This study aims to analyze the effect of self-confidence on mathematics learning outcomes of grade 8A students at SMP Ta’mirul Islam Surakarta. A quantitative approach was employed with a sample of 30 students selected through simple random sampling. Self-confidence was measured using a Likert scale questionnaire (16 items) based on five Lauster dimensions, while mathematics learning outcomes were obtained from mid-semester examination (UTS) scores. Instrument validity was assessed using Spearman correlation, and reliability was tested using Cronbach’s Alpha coefficient. Results showed that all 16 items were valid (r_count > 0.361) with a Cronbach’s Alpha of 0.854, indicating very high reliability. Spearman correlation analysis yielded ρ = 0.136 with a significance value of p = 0.474 (> 0.05), and simple linear regression analysis produced a regression equation of Y = 57.4787 + 0.1498X with R Square = 0.022 and significance value of F = 0.434 (> 0.05). These results indicate that although there is a positive effect of self-confidence on mathematics learning outcomes, the effect is very weak and statistically not significant. Only 2.2% of the variance in mathematics learning outcomes is explained by self-confidence, while the remaining 97.8% is influenced by other factors, including cognitive ability, teaching methods, learning motivation, learning environment, and the context of Islamic adab-based education that characterizes the research school.